2018
DOI: 10.1155/2018/7954816
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Liver Nodules Mimicking Metastatic Disease as Initial Presentation of Multiple Myeloma

Abstract: Multiple myeloma is a malignant clonal proliferation of plasma cells in the bone marrow preceded by monoclonal gammopathy of undetermined significance. Initial presentation of multiple myeloma as extramedullary spread in soft tissues particularly in the liver is uncommon. We report a case of a 74-year-old African American female who presented with epigastric pain, hematemesis, elevated alkaline phosphatase, and gamma-glutamyl transferase. Initial impression was peptic ulcer disease; however, ultrasound and CT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…omas et al reported that, in an autopsy series including 64 patients, 40% had plasma cell infiltration of the liver [2,3]. Liver involvement may be nodular, sinusoidal, or diffuse or may be in a mixed pattern [4]. Soft tissue involvement may…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…omas et al reported that, in an autopsy series including 64 patients, 40% had plasma cell infiltration of the liver [2,3]. Liver involvement may be nodular, sinusoidal, or diffuse or may be in a mixed pattern [4]. Soft tissue involvement may…”
Section: Discussionmentioning
confidence: 99%
“…Thomas et al reported that, in an autopsy series including 64 patients, 40% had plasma cell infiltration of the liver [ 2 , 3 ]. Liver involvement may be nodular, sinusoidal, or diffuse or may be in a mixed pattern [ 4 ]. Soft tissue involvement may be seen due to decreased expression of adhesion molecules, downregulation of chemokine receptors, downregulation of tetraspanins, increased heparanase-1 expression, angiogenesis, and mutations in alternative or classical nuclear factor-kB pathways [ 4 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This type of presentation is often described in imaging studies as multiple nodular hepatic lesions mimicking metastatic tumours. It is often associated with poor prognosis, despite treatment efforts [2][3][4]. Infiltrative liver disease, due specifically to malignant infiltration by plasma cells, is also rare at the time of diagnosis, unless the presentation is due to an aggressive form of multiple myeloma manifesting as primary plasma cell leukemia [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…Extramedullary multiple myeloma (EMM) is a malignancy of clonal plasma cells affecting extraosseous sites. Liver involvement can be seen in the late‐stage of disease . Most of the cases present as diffuse infiltrative lesions other than a focal space‐occupying mass .…”
Section: Introductionmentioning
confidence: 99%